The swan princess triple feature [videorecording (DVD)] - Rich, Richard (Sony Pictures Home Entertainment, 2014)
The swan princess: The beautiful Princess Odette is transformed into a swan by an evil sorcerer's spell (which can only be broken by a vow of everlasting love) and held captive at an enchanted lake. There, she befriends Jean-Bob the frog, Speed the turtle and Puffn the bird. Despite their struggle to keep the princess safe, these good-natured animals can do nothing about the sorcerer's spell.